Psychological and Behavioural Drivers of Short-Term Investment Intentions - Mankuroane, Evodia; Heerden, Wilme van; Ferreira-Schenk, Sune; Dickason-Koekemoer, Zandri (International Journal of Economics and Financial Issues, 2022)
Analysing the factors that influence the short-term investment intentions of investors is critical for investment institutions. If investment institutions are informed about these factors they can create a framework to more accurately profile their clients to provide clients with the desired liquidity, maturity dates and desired risk and return expectations. Risk tolerance is one of the elements that has been used over time to profile investors, however, this paper found that other factors should also be included. Therefore, this article aimed to determine what drives investors’ short-term investment intentions following a more sociological and behavioural approach by including investor personality traits, behavioural finance biases and investors’ risk tolerance behaviour. Secondary data was obtained from a private investment firm surveying private investors in South Africa. Male investors were also more likely to invest in the short-term compared to female investors. Several personality traits, risk tolerance and a single behavioural finance bias were found to influence investor intentions to invest in the short-term. It is therefore recommended to portfolio management companies that several sociological and behavioural variables do explain whether investors will be willing to invest in short-term or more long-term investment portfolios.